THE EFFECT OF LEVERAGE, RETURN ON EQUITY, SALE, CAPITAL EXPENDITURE, ASSET TURNOVER, AND WORKING CAPITAL EXPENDITURE ON FINANCIAL DISTRESS - Anges, Caney; Supriyanto, Supriyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Abstrak This quantitative research aims to determine the effect of leverage, return on equity, sales, capital expenditure, asset turnover, and working capital expenditure on financial distress in transportation sector companies listed on the Indonesia Stock Exchange from 2019 to 2022. The independent variables used in this study are financial distress. Financial distress refers to the stage of declining financial conditions of a company that can be predicted through both internal and external factors, while the dependent variables in this study include the firm life cycle (leverage measured by the debt assets ratio, return on equity measured by net profit and company equity, sales, capital expenditure, asset turnover measured by sales, and working capital expenditure). This study uses a quantitative approach with regression analysis. Secondary data were obtained and analyzed using the Eviews program. The results of the tests showed that variables X1 (leverage), X2 (ROE), X3 (sales), and X4 (capital expenditure) do not have a significant effect on financial distress, while variables X5 (asset turnover) and X6 (working capital expenditure) have a significant effect. This research can help company management make decisions related to financial strategies to avoid or address financial distress. Keywords: Leverage, Return on Equity, Sales, Capital Expenditure, Asset Turnover, Working Capital Expenditure, Financial Distress